ENHANCING TEACHERS' INNOVATIVE BEHAVIOR THROUGH ORGANIZATIONAL CULTURE STRENGTHENING, INFORMATION AND COMMUNICATION TECHNOLOGY LITERACY, AND WORK MOTIVATION - Astuti, Natalia Tri; Hardhienata, Soewarto; Suhardi, Eka (Yayasan Education and Social Center, 2024)
This study aims to formulate strategies and methods to enhance teachers' innovative behavior through a structural equation modeling analysis of the causal relationships between teachers' innovative behavior and organizational culture, ICT literacy, self-efficacy, and work motivation, as input and recommendations in the field of education. This quantitative research employed path analysis using Smart-PLS, followed by SITOREM analysis. Data was collected through questionnaires and analyzed using F-test, t-test, and multicollinearity test. The sample in this study consisted of 153 English teachers in vocational high schools in Depok City, West Java Province. The results showed that innovative behavior was influenced by organizational culture and ICT literacy, but not by self-efficacy and work motivation. Meanwhile, work motivation was influenced by organizational culture and self-efficacy, but not by ICT literacy. It is important for teachers to have high self-efficacy and good ICT literacy skills, work in an environment with a supportive organizational culture, and have high work motivation. Improving teachers' innovative behavior is an ongoing process that requires commitment and effort from various parties. Therefore, appropriate strategies and methods in the implementation of learning are expected to create a conducive learning and teaching environment so that teachers can be more innovative and effective, and also contribute to improving the quality of learning